Legal Protection for Children Working as Domestic Workers - Elfira Salma; Muh. Ali Masnun (Universitas Negeri Surabaya, 2024)
Domestic workers currently still do not have proper legal certainty as workers in general. Especially for child workers who work in this job, their dignity is not guaranteed to obtain their rights as workers and as children. Often children who work as domestic workers experience discrimination and violence. Based on Article 28B Paragraph (2) of the 1945 Constitution, children have the right to survival, growth, and development, as well as protection from violence and discrimination. This study aims to analyze the urgency of regulating legal protection for children who work as domestic workers and analyze legal protection efforts for children who work as domestic workers. This research uses normative legal research methods. The types of approaches used are statutory approaches and conceptual approaches. Based on the results and discussion of the research, the urgency of legal protection for children working as domestic workers is because children are part of human rights as stated in Article 52 Paragraph (1) of the Human Rights Law. Due to the innocent nature of children, they are vulnerable to acts of exploitation, violence, discrimination, and human trafficking. In addition, there is legal vagueness in the Permenaker PPRT in providing protection for domestic workers. Until now, legal protection efforts by the government have only been through Presidential Decree No. 59 of 2002 and the UUPA.